IMPLEMENTASI KEBIJAKAN PEMERINTAH TERHADAP PENANGGULANGAN HIV DAN AIDS DI KECAMATAN MARITENGNGAE KABUPATEN SIDENRENG RAPPANG - A., Abdul Jabbar; Barisan, Barisan (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2018)
This study aims to describe the process of implementing HIV and AIDS policies that have been carried out by the Sidenreng Rappang District government, especially in the District of Maritengngae and to illustrate the effect of implementing policies on HIV and AIDS prevention by using several indicators to measure policy implementation, namely policy determination indicators, implementers, targets, environment and process determination indicators. This study uses descriptive quantitative methods. The sampling technique is purposive sampling, using the Yamane formula. Data collection methods used through observation, questionnaire (questionnaire) and library techniques. The data analysis technique is that the collected data is carried out with a simple regression analysis with the help of SPSS 21 for Windows. The results of the analysis are descriptive statistics, data quality test, classic assumption test, Simple regression analysis and hypothesis testing. The results showed that, in the policy implementation variable, each indicator received a percentage value, that is, the policy determination indicators were in the category of 31.2%, the indicators of implementing provisions were in the category of ever or percentage of 29.8%, indicators of determination the target is in the ever category or a percentage of 35.8% and the environmental assessment indicator is in the ever category or a percentage of 31.5%, the indicator of process determination is in the ever category or percentage of 38.2%. On the variables of HIV and AIDS prevention, prevention efforts are in the ever category with a percentage of 39%, the handling efforts are in the ever category with a percentage of 28.4% and rehabilitation efforts in the ever category with a percentage of 25.6%. The implementation of Government Policy has an effect on HIV and AIDS in Maritengngae Sub-District, Sidenreng Rappang Regency, amounting to 50.2% and Implementation of Government Policy on HIV and AIDS Prevention in Maritengngae Sub-District, Sidenreng Rappang Regency is in a fairly good category.